Penerapan Model Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Prestasi Belajar Matematika Siswa SD - Mardiana Mardiana (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The problem formulation in this study is: (1) How to apply the Make A Match cooperative learning model to improve math learning achievement “Mathematics Measurement Materials” in students Class VI Elementary School 45 Buton ? (2) How to improve achievement of learning “Mathematics Measurement Materials” using cooperative learning model type Make A Match in students Class VI Elementary School 45 Buton ?